2012
DOI: 10.1128/jvi.01655-12
|View full text |Cite
|
Sign up to set email alerts
|

CTCF Occupation of the Herpes Simplex Virus 1 Genome Is Disrupted at Early Times Postreactivation in a Transcription-Dependent Manner

Abstract: cIn herpes simplex virus 1 (HSV-1), binding clusters enriched in CTCF during latency have been previously identified. We hypothesized that CTCF binding to CTCF clusters in HSV-1 would be disrupted in a reactivation event. To investigate, CTCF occupation of three CTCF binding clusters in HSV-1 was analyzed following sodium butyrate (NaB)-and explant-induced reactivation in the mouse. Our data show that the CTCF domains positioned within the HSV-1 genome, specifically around the latency-associated transcript (LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 46 publications
2
55
2
Order By: Relevance
“…Recent findings have shown that, during latency, the cellular CTCF protein is enriched on the two HSV CTRLs and that acetylated histone H3, an epigenetic beacon of active transcription, accumulates in the LAT region between these elements (19,(43)(44)(45). These findings suggested that CTRLs may act as boundary elements to shield the LAT locus against the spreading of repressive epigenetic modifications (29), and it was shown in short-term plasmid transfection assays that a fragment encompassing CTRL2 combines the functions of a typical insulator (19).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have shown that, during latency, the cellular CTCF protein is enriched on the two HSV CTRLs and that acetylated histone H3, an epigenetic beacon of active transcription, accumulates in the LAT region between these elements (19,(43)(44)(45). These findings suggested that CTRLs may act as boundary elements to shield the LAT locus against the spreading of repressive epigenetic modifications (29), and it was shown in short-term plasmid transfection assays that a fragment encompassing CTRL2 combines the functions of a typical insulator (19).…”
Section: Discussionmentioning
confidence: 99%
“…ChIP has shown that transcriptionally distinct regions of the virus genome are maintained by chromosomal insulators, most notably, the CCCTCbinding factor, CTCF (31). During HSV-1 reactivation, these chromatin boundary elements are released from the virus DNA (32,33). Since the release of CTCF from the virus genome is an attractive mechanism connecting external stress to HSV-1 reactivation (34,35) and the critical CCCTC-binding sites are separated by at least 3,300 nt (31), the HSV-1 DNA fragment size is not a critical aspect of these ChIP analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent demarcation in the nature of the chromatin likely arises due to binding sites for the cellular insulator protein CCCTC-binding factor (CTCF) on the viral genome. Interestingly, CTCF eviction coincides with reactivation (Ertel et al, 2012; Washington et al, 2018b), and depletion of CTCF in vivo promotes reactivation (Washington et al, 2018a). Furthermore, one important binding site of CTCF, known as CTRL2, lies downstream of the LAT enhancer and separates it from the nearby lytic ICP0 gene (Amelio et al, 2006b).…”
Section: Latent Viral Chromatin Structure: Silent But Poised?mentioning
confidence: 99%
“…It remains unclear if JNK plays a similar mechanistic role following explant of latently infected ganglia, and, as a whole, very little is known about the mechanisms linking cell signaling pathways and changes in viral chromatin following axotomy. However, a number of important observations about the viral chromatin have been made using the explant model, including changes in histone post-translational modification and changes in CTCF binding (Ertel et al, 2012; Washington et al, 2018b). Most notably, it has been shown that, following axotomy, there is a transient increase in the enrichment of euchromatic histone markers (acetylated H3K9/K14) at IE gene promoters (Amelio et al, 2006a).…”
Section: Axotomy/explantmentioning
confidence: 99%
See 1 more Smart Citation